Adolescents’ Narratives of Trauma, Violence, and Identity Development: A descriptive–exploratory approach - Vena Annisa Rudianty; Gina Luthfiah; Rifana Purnama (STIKep PPNI Jawa Barat, 2026)
Background: Past traumatic experiences are associated with psychosocial challenges and mental health outcomes. In nursing practice, trauma particularly sexual violence may have long-term psychological effects that shape individuals’ well-being and self-perception, including aspects of identity. Concurrently, sexual orientation diversity has become increasingly visible within Indonesian society, underscoring the need for trauma-informed, non-judgmental nursing care that supports psychological health without pathologizing sexual orientation Objective: This study aims to explore adolescents lived experiences of trauma and violent behavior and how these experiences influence their perceptions and understanding of sexual orientation. Methods: This qualitative study used a descriptive–exploratory approach. Data were collected through in depth interviews with 6 informants selected using snowball sampling. Data analysis was conducted using the Colaizzi’s method to identify emerging themes from participants lived experiences Results: Participants described past traumatic experiences, including loss of loved ones, parental separation, sexual violence, and perceived lack of parental support, as important contexts shaping their psychological well-being, interpersonal relationships, and self-understanding during adolescence. These findings reflect participants’ personal perceptions and lived experiences rather than causal changes in sexual orientation. Conclusion: This study highlights adolescents’ narratives of how traumatic experiences inform their psychosocial well-being and identity-related reflections. The findings underscore the importance of trauma-informed, non-pathologizing nursing care that acknowledges adolescents’ lived experiences and supports holistic psychological development